Antifungal Effects of Volatiles Produced by Bacillus subtilis Against Alternaria solani in Potato - Zhang, Dai; Yu, Shuiqing; Yang, Yiqing; Zhang, Jinglin; Zhao, Dongmei; Pan, Yang; Fan, Shasha; Yang, Zhihui; Zhu, Jiehua (Frontiers in Microbiology, 2020)
Antifungal activities of plant beneficial Bacillus have been widely studied in recent years. Numerous studies have studied the antifungal mechanisms of soluble non-volatile bioactive compounds such as lipopeptides and proteins produced by Bacillus against soil-borne diseases. However, the antagonistic mechanisms of volatile organic compounds (VOCs) from Bacillus against air-borne phytopathogens are still largely unknown and the function of Alternaria solani pathogenic genes has not been well identified. Here, we first isolated a Bacillus strain with strong antifungal activity and finally identified it as B. subtilis ZD01. Then the antagonistic mechanisms of VOCs produced by strain ZD01, against A. solani, an air-borne fungal pathogen which can cause early blight diseases of potato were studied. We showed that VOCs produced by strain ZD01 can reduce the colony size, mycelial penetration and can cause serious morphological changes of A. solani. Scanning electron microscope (SEM) observation showed that VOCs released by ZD01 could cause more flaccid and gapped hyphae of A. solani. Also, we found that VOCs produced by ZD01 can inhibit the conidia germination, reduce the lesion areas and number of A. solani in vivo significantly. Meanwhile, based on gas chromatography/mass spectrometry (GC/MS) analysis, 29 volatile compounds produced by strain ZD01 were identified. Out of 29 identified VOCs, 9 VOCs showed completely growth inhibition activities against A. solani. Moreover, we identified two virulence-associated genes (slt2 and sod) in A. solani. slt2 is a key gene which regulating the mycelial growth, penetration, sporulation and virulence in vivo in A. solani. In addition, sod plays a significant role in the SOD synthetic pathway in A. solani. Results from qRT-PCR showed that the transcriptional expression of these two genes was down-regulated after treated by VOCs produced by ZD01. These results are useful for a better understanding of the biocontrol mechanism of Bacillus, and offer a potential method for potato early blight disease control.